(untitled) (Conferencea, 2023)
In the modern world, the creation of information and public opinion is the most important lever of democratic governance. Any information that is transmitted as a result of communication between representatives of the press service and journalists is a necessary and necessary component for maintaining the stability of democratic governance. A representative of the press service is a specialist who plans and implements certain events, as a result of whose qualified work one can create goodwill and trust in a particular organization in society. This is a two-way communication, when people share their opinions and opinions on issues of interest. In the process of providing information to the public, the role of the speaker-judge should be taken into account. Informing the population in a simple and understandable language about ongoing processes and decisions in court and, in general, about changes in legislation is one of the necessary elements in terms of observing the principle of publicity of legal proceedings.